Analysis of Phytoplankton on The Common Carp (Cyprinus carpio) Pond and Tilapia (Oreochromis niloticus) Pond at IBAT Punten, Batu, East Java - Arfiati, Diana; Purwanti, Purwanti; Permanasari, Setya W. A.; Puspitasari, Asthervina Widyastami (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Phytoplankton plays an important role in the aquatic ecosystem for supporting the survival of organisms, such as zooplankton and fish. The aim of this research was to observe the phytoplankton in the common carp ponds and tilapia ponds with water quality parameters at IBAT Punten, Batu, East Java. The survey method was used in this research. The water quality assay was temperature, brightness, pH, DO, CO2, Nitrate, and Orthophosphate, and the phytoplankton analysis was phytoplankton abundance, diversity index, dominance index, relative abundance, similarity index, and evenness index. The water quality on the carp ponds and tilapia ponds was quite good for common carp and tilapia growth. The average of phytoplankton abundance in common carp ponds were 1538 cell/ml which classified oligotrophic and tilapia ponds were 4900 cell/ml which included mesotrophic respectively, diversity index was moderate in both ponds, no dominance specific phytoplankton in both ponds the relative abundance in both ponds showed different phytoplankton availability, the similarity, and evenness index showed the same in both ponds and evenly on tilapia ponds and equally on common carp pond respectively. The carbon dioxide (CO2), nitrate, and orthophosphate have a strong correlation to phytoplankton abundance with value 0.882; 0.949; and 0.967 respectively. In the future, pond management will be needed in IBAT Punten with growing natural food.